Revealing values in a complex environmental program: a scaling up of values-based indicators. (15th October 2016) - Podger, Dimity; Hoover, Elona; Burford, Gemma; Hak, Tomas; Harder, Marie K.
Abstract: Ethical values such as trust, compassion and equality are core to the way many pro-environmental organizations function, whether or not they claim these are key to their success. Mainstream sustainability indicators do not, however, explicitly acknowledge this values dimension. In this paper we describe a replicable approach that has successfully been used to develop values-based indicators and assessment tools within an emancipatory research paradigm, in an EU-funded project characterized by close partnership between civil society organizations (CSOs) and university-based research groups. We outline the methodology used to develop values-based indicators, and then demonstrate how the resulting indicators were used systematically to evaluate a national program of youth leadership within a large Mexican civil society organization promoting reforestation. We reflect on this illustrative example in relation to wider conversations about values and sustainability.